Rapid Response of the Yield Threshold and Turgor Regulation during Adjustment of Root Growth to Water Stress in Zea mays. - Frensch, J. (1995)
Responses of cortical cell turgor (P) following rapid changes in osmotic pressure ([pi]m) were measured throughout the elongation zone of maize (Zea mays L.) roots using a cell pressure probe and compared with simultaneously measured root elongation to evaluate: yield threshold (Y) (minimum P for growth), wall extensibility, growth-zone radial hydraulic conductivity (K), and turgor recovery rate. Small increases in [pi]m (0.1 MPa) temporarily decreased P and growth, which recovered fully in 5 to 10 min. Under stronger [pi]m (up to 0.6 MPa), elongation stopped for up to 30 min and then resumed at lower rates. Recoveries in P through solute accumulation and lowering of Y enabled growth under water stress. P recovery was as much as 0.3 MPa at [pi]m = 0.6 MPa, but recovery rate declined as water stress increased, suggesting turgor-sensitive solute transport into the growth zone. Under strong [pi]m, P did not recover in the basal part of the growth zone, in conjunction with a 30% shortening of the growth zone. Time courses showed Y beginning to decrease within several minutes after stress imposition, from about 0.65 MPa to a minimum of about 0.3 MPa in about 15 min. The data concerning Y were not confounded significantly by elastic shrinkage. K was high (1.3 x 10-10 m2 s-1 MPa-1), suggesting very small growth-induced water potential gradients.